2007
DOI: 10.1111/j.1365-2214.2007.00771.x
|View full text |Cite
|
Sign up to set email alerts
|

Early weaning is related to weight and rate of weight gain in infancy

Abstract: Early weaning is related to rapid weight gain in infancy. This may have implications for childhood obesity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
55
1
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(62 citation statements)
references
References 21 publications
4
55
1
1
Order By: Relevance
“…Both early (younger than 6 months) and late (older than 6 months) complementary feeding can have undesirable Includes cold cuts, bacon, sausage health outcomes [63]. Evidence suggests that early feeding of complementary foods puts infants at a higher risk for microbial infections, [51] and excess weight gain later in life [25][26][27]. Late feeding of complementary foods and/or reliance on poor quality foods increases an infant's risk of malnutrition, poor growth, and micronutrient deficiencies [64] and is a major cause of preventable mortality in young children [50].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both early (younger than 6 months) and late (older than 6 months) complementary feeding can have undesirable Includes cold cuts, bacon, sausage health outcomes [63]. Evidence suggests that early feeding of complementary foods puts infants at a higher risk for microbial infections, [51] and excess weight gain later in life [25][26][27]. Late feeding of complementary foods and/or reliance on poor quality foods increases an infant's risk of malnutrition, poor growth, and micronutrient deficiencies [64] and is a major cause of preventable mortality in young children [50].…”
Section: Discussionmentioning
confidence: 99%
“…These recommendations support optimal growth and development, the establishment of healthy eating habits and the prevention of obesity. Specific feeding practices and dietary factors associated with overweight/obesity in infants and young children such as lack/short duration of breastfeeding [20][21][22][23], early introduction to complementary foods [24][25][26][27], intake of sugar-sweetened beverages [28][29][30], and low fruit and vegetable consumption [31,32], are now recognized to begin in infancy [9], and have been a focus in describing early dietary patterns in infants and young children from national dietary intake surveys in the United States (US) [33].…”
Section: Introductionmentioning
confidence: 99%
“…Among women who had ceased breast-feeding before 6 months of age, the reason most commonly cited was that they did not have enough breast milk (56%), and that the child had lost interest (34%). 11 The retrospective design of many existing studies on infant feeding has been criticised by a number of authors as it may lead to misclassification of feeding practices and data that contain inaccuracies related to the nature of maternal recall of feeding behaviours (for example Donath and Amir, 12 Sloan et al 13 Lin et al, 14 Burnham et al 15 ). In a review article Li and colleagues 16 reported that even with a short recall period (less than 3 years) the majority of mothers could only recall the duration of breast-feeding to within a month of the actual duration, and the recall of mothers relating to timing of cessation of breast-feeding was even more inaccurate.…”
Section: Introductionmentioning
confidence: 98%
“…The transition from an exclusively milk-based diet to solid foods is a critical stage in the development of food behavior and also for the infant's growth [26] and long-term health [27]. The establishment of eating habits during weaning seems to be influenced by breastfeeding, weaning practices and repeated exposure.…”
Section: Establishment and Directed Changes In Food Preferencesmentioning
confidence: 99%